(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In order to improve one’s overall well-being, these psychological treatments aim to do manythings. The study’s goal was to determine whether and how stress-reduction programmes at OsmaniaUniversity improved students’ mental health and school performance. A control group and pre- and posttestswere part of the quasi-experimental methodology used. This is why we split 40 students fromTehran’s Osmania University into two groups, an experimental group and a control group, using aconvenience sampling technique. “Both groups were given a pre-test consisting of 84 questions onmental health and academic vigour using two separate questionnaires. Then, the test group participatedin 10 sessions of stress management training while the control group got no treatment. After collectingpost-test results from both groups, we examined them using descriptive and inferential statistics inSPSS-26.The results demonstrated that students’ academic liveliness and psychological well-beingimproved considerably after receiving training in stress management skills (p 0.001).This researchindicated that teaching the skills for dealing with stress was an effective technique to help studentsexposed to high stress and pressure due to its high efficiency, especially when held in groups, its cheapcost, and its acceptability by the people.